Corruption and tax non-compliance model : an investigation on individual taxpayers in Yemen - Abd Obaid, Mohammed Mahdi (2017)
Governments around the world continuously attempt to improve the level of tax compliance especially those in countries which face a high level of tax noncompliance. Yemen is one of these countries in which tax non-compliance has been reported to be at a high level during the last few decades. This study empirically investigates the influence of perception of corruption in the government, tax rate, penalty rate, income level and education level on individual taxpayer’s noncompliance behaviour in Yemen. This study is underpinned by the social influence theory, and further supported by the deterrence theory and cognitive learning theory. The data, which were collected through survey questionnaires, were analysed using multiple regression analysis and other statistical techniques. A total of 400 questionnaires were distributed that yielded 264 usable questionnaires. The results reveal that there is a positively significant relationship between perception of corruption in the government, tax rate and penalty rate and tax non-compliance, whereas the relationship between income level and tax non-compliance is negatively significant and the relationship between education level and tax non-compliance is insignificant. This study concludes with the theoretical implications and practical recommendations for the Yemeni Government in order to improve tax collection such as to develop and implement more stringent enforcement strategies to combat corruption in the administration and improve the tax system in terms of penalty rate and tax rates. In addition, the Yemen Tax Authority should play a more proactive role to encourage and educate individual taxpayers by enhancing their knowledge on taxation. This study also highlights several limitations and suggests future studies that can be conducted in this area.